2013
DOI: 10.3736/jintegrmed2013046
|View full text |Cite
|
Sign up to set email alerts
|

Investigating short- and long-term transfer effects of a Taiji beginner course in participants' daily life

Abstract: OBJECTIVE:In recent years research investigating various health benefits of Taiji practice has markedly increased. Despite this growing scientific interest, essential questions such as to what extent a Taiji course may exert noticeable effects in participants' everyday life, what these effects are, and how and where potential transfer effects occur, have hardly been considered. The aim of our study was to explore transfer effects from a Taiji course into participants' daily lives. METHODS:We conducted a longit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Although there is no direct connection between postural awareness and pain, postural awareness may establish the basis for the process of changing habitual postural and movement patterns, that is, postural awareness can be considered a key prerequisite for postural control 35 ; and increasing postural awareness should facilitate postural control. At least for Tai Chi, previous research has found compelling evidence for improvements in postural control as indicated by increases in body awareness, 36,37 improvements of balance and reduced falls, [38][39][40] alterations in muscle tone, 41 and better kinesthetic control. 42,43 Similar findings have been reported for yoga, as witnessed by improvements in proprioceptive acuity in chronic neck pain 44 and in postural control in schizophrenia 45 or older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no direct connection between postural awareness and pain, postural awareness may establish the basis for the process of changing habitual postural and movement patterns, that is, postural awareness can be considered a key prerequisite for postural control 35 ; and increasing postural awareness should facilitate postural control. At least for Tai Chi, previous research has found compelling evidence for improvements in postural control as indicated by increases in body awareness, 36,37 improvements of balance and reduced falls, [38][39][40] alterations in muscle tone, 41 and better kinesthetic control. 42,43 Similar findings have been reported for yoga, as witnessed by improvements in proprioceptive acuity in chronic neck pain 44 and in postural control in schizophrenia 45 or older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived benefits of these interventions were manifold and included body-related effects, such as improvement of motor coordination, physical function or looseness, mind-related effects, such as improvements in self-efficacy and stress management and mind-body-related effects, such as increase of body awareness, relaxation or the ability to make self-corrections [ 42 , 43 ].…”
Section: Empirical Evidence For the Psc Modelmentioning
confidence: 99%
“…; Schitter et al. ), emphasizing the increase in effects regarding self‐compassion beyond the designated training period. Behavior and lifestyle are being discussed not only with regard to treatment of depression, but also to its onset (Sarris et al.…”
Section: Discussionmentioning
confidence: 99%